2001
DOI: 10.1248/cpb.49.652
|View full text |Cite
|
Sign up to set email alerts
|

New Insulinomimetic Zinc(II) Complexes of .ALPHA.-Amino Acids and Their Derivatives with Zn(N2O2) Coordination Mode.

Abstract: Key words zinc(II) complex; amino acid; insulinomimetic activity; NIDDM; blood glucose normalizing effect; glucose tolerance test Zinc(II) ion is known to be one of the important essential trace elements found in biological systems and also in many metalloproteins and metalloenzymes which exist in living organisms. Physico-chemical properties of a zinc(II) ion, which functions as a Lewis acid, is entirely unlike those of vanadium ions with a redox property and insulinomimetic activity. Among many pharmacologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 13 publications
1
46
0
4
Order By: Relevance
“…9,10) The Zn(II) complexes were purified with hot water to obtain bis(thiophene-2-carboxylato)zinc (Zn(tc) 2 ), with 2-propanol to obtain bis(a-furoic acidato)zinc (Zn(fa) 2 ), and with methyl alcohol to obtain bis(thiophene-2-acetato)zinc (Zn(ta) 2 ) and bis(pyrrole-2-carboxylato)zinc (Zn(pc) 2 ).…”
Section: Synthesis Of 4 Zn(ii) Complexesmentioning
confidence: 99%
“…9,10) The Zn(II) complexes were purified with hot water to obtain bis(thiophene-2-carboxylato)zinc (Zn(tc) 2 ), with 2-propanol to obtain bis(a-furoic acidato)zinc (Zn(fa) 2 ), and with methyl alcohol to obtain bis(thiophene-2-acetato)zinc (Zn(ta) 2 ) and bis(pyrrole-2-carboxylato)zinc (Zn(pc) 2 ).…”
Section: Synthesis Of 4 Zn(ii) Complexesmentioning
confidence: 99%
“…1) We reported that Zn(II) complexes with nicotinamide, maltol, amino acids, picolinic acid, picolinamide, and their derivatives have high insulinomimetic activities in in vitro and in vivo studies. [2][3][4][5][6][7] However, these complexes were effective in showing the lowering effect of blood glucose by daily intraperitonial injections to type 2 diabetes mellitus. When aiming at the clinical use of the complexes, it is essentially important to find complexes that are effective on oral administration.…”
mentioning
confidence: 99%
“…Among the wide variety of zinc(II)-amino acids or -peptides complexes prepared, [Zn(thr) 2 ] complex 14 showed the functions, such as blood glucose lowering effect and HbA 1c normalizing effect, suggesting that it is a clinically useful agent to treat type 2 diabetes.…”
Section: Dinuclear Vanadyl Complexes Among Many Vanadyl Complexes Amentioning
confidence: 99%